Anti-inflammatory effects of LCB 03-0110 on human corneal epithelial and murine T helper 17 cells - Truong, Do Vinh; Yang, Beom Seok; Song, Chiman (대한약리학회, 2025)
Dry eye disease (DED) is a complicated disorder that impacts ocular surface and tear-film stability. Inflammation has recently been reported as the core mechanism and main therapeutic target of DED. Although anti-inflammatory drugs have been developed, they still have limited efficacy and various side effects. Recent reports have suggested that kinase inhibitors are beneficial for relieving inflammation. Therefore, this study aimed to investigate the anti-inflammatory effects of LCB 03-0110, a multi-tyrosine kinase inhibitor, on representative cell-based models (HCE- 2 and Th17 cells) of DED. While tacrolimus and tofacitinib, two different anti-inflammatory drugs that have entered clinical trials for DED treatment, did not induce any anti-inflammatory responses in HCE-2 cells, LCB 03-0110 significantly suppressed the phosphorylation of P38 and ERK and reduced the expression levels of IL-6 and IL-8 in HCE-2 cells treated with either LPS or poly(I:C). Moreover, LCB 03-0110 notably decreased the expression level of IL-17A in Th17 cells in a dose-dependent manner, whereas tofacitinib promoted IL-17A production at low concentrations but inhibited its expression at concentrations greater than 1 μM. In addition, LCB 03-0110 was found to be non-toxic to both HCE-2 and Th17 cells. In conclusion, these results suggest that LCB 03-0110 would be a promising drug candidate for the treatment of DED because of its advantages over tacrolimus and tofacitinib.